2015
DOI: 10.1007/s11130-015-0478-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Metabolites Composition and Biological Activities of Phyllanthus niruri Extracts Prepared by Different Drying Methods and Solvents Extraction

Abstract: The study investigated the changes in the metabolite, antioxidant and α-glucosidase inhibitory activities of Phyllanthus niruri after three drying treatments: air, freeze and oven dryings. Water extracts and extracts obtained using different solvent ratios of ethanol and methanol (50, 70, 80 and 100%) were compared. The relationships among the antioxidant, α-glucosidase inhibitory activity and metabolite levels of the extracts were evaluated using partial least-square analysis (PLS). The solvent selectivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…Previously, Lin et al [33] found that there were insignificant differences in the α-glucosidase activity of Rabdosia serra leaf prepared by AD and SD methods. While Mediani et al [13] reported that AD extracts of Phyllanthus niruri exhibited higher α-glucosidase activity compared to OD α-GLUCOSIDASE INHIBITORY ACTIVITY OF IPOMOEA AQUATICA extracts. Differences in our findings and previous reports are probably due to differences in plant composition (i.e., metabolites, water content, and cell structure).…”
Section: Effect Of Different Drying Treatments and Solvents On Tpc Anmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, Lin et al [33] found that there were insignificant differences in the α-glucosidase activity of Rabdosia serra leaf prepared by AD and SD methods. While Mediani et al [13] reported that AD extracts of Phyllanthus niruri exhibited higher α-glucosidase activity compared to OD α-GLUCOSIDASE INHIBITORY ACTIVITY OF IPOMOEA AQUATICA extracts. Differences in our findings and previous reports are probably due to differences in plant composition (i.e., metabolites, water content, and cell structure).…”
Section: Effect Of Different Drying Treatments and Solvents On Tpc Anmentioning
confidence: 97%
“…Previously, PLS has been successfully used to correlate the bioactivity with phytochemical constituents. [13,14] In PLS, the data are separated into two blocks, the X-block represents the predictor variables (NMR chemical shift of the metabolites) and the Y-block represents the response variables (bioactivity). [40] By using PLS, the relationship between bioactivities (1/IC 50 of α-glucosidase inhibitory and TPC) and the metabolites in the ethanol extracts can be established.…”
Section: Classification Of I Aquatica Extracts In Different Drying Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding phenolic compounds, mainly flavonoids such as kaempferol derivatives have been reported in S. reticulata [2] [7]; quercetin derivatives in P. alliacea [8] and P. niruri [9]; whereas caffeic acid derivatives and ellagitannins have also been reported in P. niruri [10]. Flavan-3-ols, including catechin and epicatechin monomers have been reported in P. niruri [11], whereas no detailed studies on proanthocyanidin oligomers have been performed in any of these three species.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, this herb contains chemical substances including lignin, glycoside, alkaloid, ellagitannin, terpenoid, phenylpropanoid, flavonoid and polyphenol [6]. Instead of this herb has been studied its pharmacological activity in the treatment of bladder infection, as immunomodulator, anti-inflammatory and antiviral agents [7,8], to date, there is no report about this species to be used as an endophyte source. Hence, it is interesting to study more about extraction and biological testing of fungal endophyte from Phyllanthus niruri.…”
Section: Introductionmentioning
confidence: 99%